Over expression of Voltage Dependent Anion Channel 2 (VDAC2) in muscles of electrically stunned chickens - Abu Samah, Norshahida; Amid, Azura; Yusof, Faridah (IIUM Press, 2011)
Water bath stunning is a common practice in commercial slaughterhouses. Such treatment is economic and in line with animal welfare practice. However, the conditions applied for the stunning process may vary from a slaughterhouse to another slaughterhouse. Such a loose regulation on the stunning procedure has opened up doors for food adulteration such as over dose stunning. In this study, a simple and reliable approach using proteomics have been developed to study the effect of different currents and voltages in stunning on the protein expression of the chickens. Protein profiles of the chickens were constructed in order to detect any differences in protein expression and modifications. The different voltage studied were 10 V, 40 V and 70 V while the values for current studied were 0.25 A, 0.5 A, and 0.75 A. After the proteomics analyses using 2D Platinum ImageMaster 6.0 and Matrix-assisted laser desorption ionization- time of flight (MALDI TOF) spectrometry identification, Voltage dependent anion channel 2 (VDAC2) was identified to be over expressed in the muscle sample of over stunned chicken. The over expression of VDAC2 was confirmed at the transcriptional level of RNA expression. Real Time PCR showed that all over stunned samples contained higher mRNA expression level for VDAC2 genes. The mRNA level of VDAC2 was upregulated by 59.87 fold change when normalized with housekeeping gene. In conclusion, VDAC2 could serve as potential biomarkers for identification of electrically stimulated chickens. The existence of these biomarkers will help to monitor the slaughtering and stunning process in the future. It will revolutionize the food authentication field and give a new breathe to the meat industry.